Nutritional status of adolescent girls in Bangladesh: findings of a community based survey (South East Asia Journal of Public Health, 2016)
Poverty, large population, socio- economic inequalities and inadequate access to proper health care facilities are the key causes of under nutrition in Bangladesh. Adolescents are the most vulnerable group for under nutrition and having great consequence as they will be parent in future. Studies on nutritional status of adolescent girls are fewer in number and have great effect for intervention. The objective of this study was to assess the nutritional status and predisposing factors of under nutrition among the adolescent girls in Bangladesh. A community-based cross-sectional survey was carried out from July to December 2013. Adolescent girls were the study population. Data was collected by face to face interview at household level. According to BMI category (kg/m2) the prevalence of under-weight (BMI